Answer:
36
Explanation:
To answer this question, we need to first understand the notation (f · x)(-2). This is a composite function, and another way to write this is f(g(-2)). This means that we have to find g(-2) and apply the function f to whatever this value is. Let's start by finding g(-2):
![g(x)=x-2\\g(-2)=-2-2\\g(-2)=-4](https://img.qammunity.org/2023/formulas/mathematics/high-school/wmo56skw3wkztcz1xrbt765vcn4056sewi.png)
Now that we know g(-2) is -4, we can apply this to f:
![f(x)=x^2-4x+4\\f(-4)=(-4)^2-4(-4)+4\\f(-4)=16-(-16)+4\\f(-4)=16+16+4\\f(-4)=36](https://img.qammunity.org/2023/formulas/mathematics/high-school/h79cw6grelgtf1ocg9tgg54uilnuthdnrj.png)
Therefore, our answer is 36